Soil net nitrogen mineralisation across global grasslands - A. C. Risch (Nature Portfolio, 2019)
Nitrogen mineralisation (Nmin), an important index of soil fertility, is often determined in the laboratory, with an uncertain relationship to Nmin under field conditions. Here the authors show that combining laboratory measurements with environmental data greatly improves predictions of field Nmin at a global scale.